PEMBUATAN MODEL LENGAN INFUS ALTERNATIF SEBAGAI ALAT PERAGA PRAKTIKUM PEMASANGAN INFUS - Catur Anita Sari; Linda Y Salawane (JOMIS (Journal of Midwifery Science), 2025)
Basic Midwifery Skills Practicum is a basic skill that must be mastered by health workers, especially midwives and nurses, such as installing IV drips. Infusion phantoms have been widely circulated in Indonesia with the same feature, namely only for administering infusions, so that when they go directly to patients. For this reason, researchers want to develop a device for infusion installation that is accompanied by the feature of blood vessels bursting and swelling when injecting too deeply. Apart from that, researchers also added a training feature to intra-cutaneous injection. Research Objective: to develop a simple infusion examination tool equipped with features for intra-cutaneous injection practice. Method: This research is a development study that produces a product using the One Shot Case Study method. The study was conducted at the Midwifery Laboratory of Poltekkes Kemenkes Sorong for 7 months, from April 1 to October 1, 2024. Results: Of the 35 respondents (Lecturer and Cilinical Instructor) who took part in the field trial, the total questionnaire score obtained was 6,758 with an ideal maximum total score of 7,350. The eligibility percentage obtained was 92%. Conclusion: A simple infusion installation trainer is very suitable for use as a tool for administering infusions in a laboratory equipped with an intra-cutaneous injection feature. It is recommended for all PLPs in Indonesia to carry out new innovations in laboratories in order to improve student skills by identifying problems that are often encountered in their respective institutions to improve the quality of their laboratories.